Gastrointestinal involvement in langerhans cell histiocytosis: consider treatment as for multi-system disease. (24th May 2012) - Williamson, H; O'neil, D; Walker, DA; Charlton, C
Abstract : Aims: Langerhans cell histiocytosis (LCH) is a rare disorder characterised by abnormal proliferation of the Langerhans cell.1 While single system disease has a good prognosis, multisystem disease often requires intensive combination chemotherapy.2 3 Gastrointestinal (GI) involvement in LCH remains rare4 and its presence alone does not fit criteria for such treatment.3 The clinical picture can vary but most often consists of bloody diarrhoea, non bloody diarrhoea or constipation, protein losing enteropathy, hypoproteinaemia and anaemia.4 5 It almost exclusively affects children below two years of age and it has been noted that over half of patients with LCH and GI involvement die within one and a half years of diagnosis.4 5 Here we describe the case of a young female who required combination chemotherapy to control her GI disease. Methods: A six month old female infant initially presented with a non-blanching erythematous rash involving the abdomen and groin, later developing bloody diarrhoea, intermittent bilious vomiting and failure to thrive. She was pale, wasted and developmentally delayed with a painless cystic lump on the occiput. There was lymphadenopathy and an enlarged spleen. Investigations revealed anaemia, thrombocytosis, elevated fibrinogen, a raised ESR and hypoalbuminaemia. Florid histiocytic inflammation of the small bowel was identified at endoscopy and a barium swallow showed narrowing of the distal duodenum and proximal jejunum without obstruction. Gut biopsies and skin samples confirmed the diagnosis of LCH. Results: Dual therapy consisting of vinblastine and prednisolone was commenced with quick regression of her bone and skin disease. The addition of mercaptopurine and methotrexate was eventually required to control her GI disease. Almost three years post diagnosis she remains on this quadruple regimen as maintenance therapy. Her current disease status is that of regressing disease although her symptoms return towards the end of treatment intervals. Discussion: The prevalence of GI involvement may be underestimated given its presentation; mild cases could be overlooked without endoscopic examination and biopsies. We may see a rise in recorded cases with increased availability of endoscopy. From our experience of this case we recommend that combination therapy is considered for cases of LCH with GI involvement.